EFEKTIVITAS KOMPETENSI KEPRIBADIAN GURU TERHADAP TINGKAT MINAT BELAJAR SISWA DI SMP SWASTA ISLAM KUALA SIMPANG KABUPATEN ACEH TAMIANG - Muhammad Wahyudi (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2018)
Quality education can be realized if there is a school with complementary elements such as teachers, infrastructure, and other administrative personnel with good quality. Without neglecting the role of other important factors, teacher quality has been found by various research studies as the most important factor in influencing education quality. The task of the teacher is not only transferring the knowledge possessed by the teacher to students with the target of conveying topics written in curriculum documents to students. As for this type of research is descriptive research. This study in the form of generated data is presented in the form of verbal words not in the form of numbers that produce descriptive data and their observed behavior